Towards a framework for assessing the sustainability of supply chains : the case of potatoes in Britain - Vasileiou, Konstantinos Z. (Cranfield University, 2002)
There is growing concern about the sustainability of food production and marketing systems when measured against a set of sometimes conflicting economic, environmental and social criteria. In this context, this research aims to develop and apply a framework to assess the sustainability of fresh produce supply chains, from farm to retail outlet, using British fresh potato production and marketing as a case study. Following a review of relevant literature, in-depth interviews were carried out with farmers, merchants and retailers to explore perceptions of the sustainability of the fresh potato supply chain over the last decade. After this, the research adopted quantitative and qualitative methods of investigation. An attempt was made to measure the changes in the performance of the fresh potato supply chain between 1990 and 2000 in an objective manner, using thirteen sustainability (economic, environmental and social) indicators. However, the d egree of the sustainability of the supply chain was measured only for 2000, because of a considerable lack of available data for 1990. Thus it was not feasible to draw conclusions on the changes of supply chain sustainability over the last decade. It was shown that the farm stage was responsible for most of the emissions to the environment and water consumption in 2000. Most of the energy was consumed at the farm and merchant stages, while the merchant stage was the most labour intensive in the supply chain. A questionnaire survey of 240 farmers, 17 merchants and 4 retailers was carried out to elicit their perceptions of the importance of selected sustainability factors influencing supply chain performance, the changes in business sustainability during the last decade, and the future of the fresh potato supply chain. The participants perceived that their business profitability has either been stable or decreased, while cost efficiency and environmental and social performance have improved. During the last 10 years, economic factors have been the key drivers for change in the supply chain, however environmental and social issues have increased in importance and are likely to do so in the future. The participants perceived that major retailers, driven by the fierce competition at the retail stage where the power base for the supply chain appears to lie, have promoted actions to improve aspects of the sustainability of the whole fresh produce supply chain, such as farm assurance schemes. This study confirmed that it is feasible to develop an approach to assess the sustainability of fresh produce supply chains over time. These sustainability indicators could be further developed and applied in the fresh potato supply chain on a regular basis in the future to provide an ongoing monitoring and evaluation of the changes in the supply chain performance in an objective manner. The developed approach could also be applied on other fresh vegetables supply chains. The study concludes that it is in the collective interest of all participants in the fresh potato supply chain to find ways to improve its economic, social and environmental performance.